2016
DOI: 10.1093/nar/gkw1276
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 promotes p63 and GRHL3 expression downstream of FOXO in mammary epithelial cells

Abstract: Bromodomain-containing protein 4 (BRD4) is a member of the bromo- and extraterminal (BET) domain-containing family of epigenetic readers which is under intensive investigation as a target for anti-tumor therapy. BRD4 plays a central role in promoting the expression of select subsets of genes including many driven by oncogenic transcription factors and signaling pathways. However, the role of BRD4 and the effects of BET inhibitors in non-transformed cells remain mostly unclear. We demonstrate that BRD4 is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 86 publications
(134 reference statements)
3
24
0
Order By: Relevance
“…Finally, we observed that JQ1 treatment profoundly inhibits RAINs expression with a stronger effect than the one observed on RUNX2 expression (Figure 8F ). This is coherent with the observation that BRD4 controls the transcription of non-coding RNAs from regulatory ENHs ( 49 , 50 ). These data describe a new family of RUNX2 associated intergenic lncRNAs and envisage a functional relationship between RUNX2 and its cognate lncRNAs in cancer.…”
Section: Resultssupporting
confidence: 90%
“…Finally, we observed that JQ1 treatment profoundly inhibits RAINs expression with a stronger effect than the one observed on RUNX2 expression (Figure 8F ). This is coherent with the observation that BRD4 controls the transcription of non-coding RNAs from regulatory ENHs ( 49 , 50 ). These data describe a new family of RUNX2 associated intergenic lncRNAs and envisage a functional relationship between RUNX2 and its cognate lncRNAs in cancer.…”
Section: Resultssupporting
confidence: 90%
“…The question remains how p53-R273H promotes NEU1 expression. It has been demonstrated that activated AKT signaling regulates a series of gene transcription pathways, including c-Myc and p63 36 . Interestingly, it has been shown that mutant p53 can activate AKT signaling by enhancing EGFR trafficking 18 .…”
Section: Discussionmentioning
confidence: 99%
“…While the frequent association of SE with master regulators may justify the recent interest in their characterization, SEs may simply be the "low hanging fruit" of enhancers that can prejudice our investigations and prevent us from identifying other important regulatory elements that can have significant impacts and effects. Instead, a differential occupancy approach as we recently described, 7,8 may provide a more effective approach to identify functionally important enhancers and their underlying transcription factor networks.…”
Section: Resultsmentioning
confidence: 99%
“…7 Similarly, we showed that the majority of BRD4enriched regions in mammary epithelial cells were associated with putative enhancers. 8 Remarkably, more than one-third of epithelial-to-mesenchymal transition-related genes showed an enrichment of BRD4 at an adjacent distal region. Overall, enhancers emerge as a common and decisive mechanism in BRD4-mediated regulation of gene transcription.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation